2022
DOI: 10.1038/s41419-021-04483-0
|View full text |Cite
|
Sign up to set email alerts
|

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth

Abstract: SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The protein lysine methyltransferase SMYD2 functions as an oncogene involved in regulating its downstream target genes through histone or non-histone methylation and suppression of p53 activity to promote the metabolism of glucose [13,17]. These factors may influence tumor-cell proliferation, apoptosis, metastasis and chemosensitivity [14,18]. In this research, SMYD2 knockdown inhibited the growth of CaSki and SiHa cells, which indicated that SMYD2 acts as a tumor "instigator" in CESC.…”
Section: Discussionmentioning
confidence: 65%
“…The protein lysine methyltransferase SMYD2 functions as an oncogene involved in regulating its downstream target genes through histone or non-histone methylation and suppression of p53 activity to promote the metabolism of glucose [13,17]. These factors may influence tumor-cell proliferation, apoptosis, metastasis and chemosensitivity [14,18]. In this research, SMYD2 knockdown inhibited the growth of CaSki and SiHa cells, which indicated that SMYD2 acts as a tumor "instigator" in CESC.…”
Section: Discussionmentioning
confidence: 65%
“…Fig. S11A-B), as reported previously (Yu et al, 2022). We therefore focused on apoptotic MC38 DCvax-IT.…”
Section: Therapeutic Dcvax-it Fails Against a T Cell-depleted Tumour ...mentioning
confidence: 75%
“…In the context of a project aimed to study the role of SMYD2 in cancer [36], SMYD2sufficient and SMYD2-deficient HT-29 cells (Figure 1A), a human colorectal cancer cell line that has been widely used for many years, were implanted into Rag1 −/− mice via subcutaneous injection, and RNA-seq analysis of HT-29 xenografts was performed (Figure 1B). Interestingly, RNA-seq data analyses revealed that transcript levels of TMPRSS2 were significantly lower in both clones of SMYD2-deficient cells as compared to WT cells (Figure 1C).…”
Section: Smyd2 Deficiency or Inhibition Results In The Downregulation...mentioning
confidence: 99%
“…HT-29 (ATCC ® HTB-38™) cells were maintained in DMEM supplemented with 10% FCS and 1% penicillin/streptomycin (P433, Sigma-Aldrich, St. Louis, MO, USA). SMYD2 knockout cell lines were established as previously described [36]. Caco-2 cells (kindly provided by Konstantin Sparrer, University Hospital Ulm, Germany) were cultivated in DMEM, additionally containing 1× MEM Non-Essential Amino Acids Solution (11140050, Thermo Fisher Scientific).…”
Section: Cell Culturementioning
confidence: 99%